Informal reckonings: conflict resolution in mediation, restorative justice and reparations - Woolford, Andrew John (A GlassHouse book, 2008)
Formal and informal justice -- Assessing informal justice -- Mediation in the informal/formal justice complex -- Restorative justice in the informal/formal justice complex -- Reparations in the informal/formal justice complex -- Informal justice counterpublics